2015
DOI: 10.1111/ans.13355
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic modalities for upper gastrointestinal leaks, fistulae and perforations

Abstract: BackgroundEndotherapy techniques are a recent addition to the suite of non‐surgical and minimally invasive strategies to manage patients with perforations, leaks and fistulae. The emergency nature of these conditions and the heterogeneity of pathologies encountered create difficulties when trying to select appropriate tools in these complex situations. The purpose of this article is to review experience at a tertiary academic centre, describe the various endoscopic tools available and the situations where they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…Conservative strategies are only reasonable for small leakages in patients with low clinical impact. In contrast, cases of large defects, severe sepsis, and bowel obstruction are rather managed surgically [7]. An endoscopic approach should be taken into consideration when an intervention is necessary and technically possible, and surgery should be avoided because of comorbidities, contraindications, or the patient's wish.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative strategies are only reasonable for small leakages in patients with low clinical impact. In contrast, cases of large defects, severe sepsis, and bowel obstruction are rather managed surgically [7]. An endoscopic approach should be taken into consideration when an intervention is necessary and technically possible, and surgery should be avoided because of comorbidities, contraindications, or the patient's wish.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 9 , 10 Several case reports have shown successful nonoperative treatment of patients' condition by use of bowel rest, intravenous antibiotics, and, in some cases, percutaneous drainage. 1 , 11 , 12 A recent report by Talbot et al 13 showed that minimally invasive endoscopic techniques for drainage of perforations, leaks, and fistulae are a successful strategy for the management of intraabdominal pathologic conditions that would otherwise require surgery. In their study, all of their patients had uncomplicated recoveries without recurrence of leaks, and they tolerated fluid diets after drain placement.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent this event, clip application, large size of indwelling stent, suture fixation and partial covered stent usage have been shown to decrease the treatment failure rates [2,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Anal pain and migration related to the stent were a significant problem and were frequently encountered when the anastomosis was within 5 cm of the anal canal. Partially covered stents have proximal and distal mesh flares for [14]. On the other hand, this feature may result in impaction of the stent to the tissue wall by excessive fibrosis and granulation tissue leading to perforation or inability to remove the stent [24,25].…”
Section: Discussionmentioning
confidence: 99%